Set the action! : creating backgrounds for compelling storytelling in animation, comics, and games - Hernandez, Elvin A. (Focal Press, 2013)
Create the Gotham for your Batman, the African savannah for your Simba, or the bustling newsroom for your Clark Kent. Background, setting, environment.whatever you call it, it is the silent character in the visual story, and a dynamic and compelling setting can define and hone the action and drama of your story. If you're in the habit of creating disembodied characters or adding backgrounds as an afterthought, Set the Action! will help you understand and utilize the importance of the setting in your narrative. Understand perspective, blocking, and color-and focus your narrative by establi.